Values and Evidence in Gender-Affirming Care - Keyes, Os (The Hastings Center report, 2024)
This commentary responds to the article “What Is the Aim of Pediatric ‘Gender-Affirming’ Care?,” by Moti Gorin, in the same issue of the journal. Gender-affirming care is often treated as exceptional and subject to heightened scrutiny. This exceptionalization results in its being held to stricter evidentiary standards than other forms of medical interventions are. But values and value judgments are inextricable from the practice of evidence-based medicine. For gender-affirming care, values shape what counts as “strong” evidence, whether the legitimacy of transgender identity is assumed versus treated as something to be investigated, how to characterize the testimonial accounts of trans and gender-nonconforming patients, and more. We argue that these kinds of questions are part of the practice of medicine, not exceptional to transgender people and gender-affirming care. However, litigation of evidence for gender-affirming care in state and national policy underscores the moral urgency of thinking carefully about what values ought to guide evidence.